Accountants in a Telecommuting Laboratory : Individual Experiences of the Benefits and Challenges in Helping Organise Post-Pandemic Work - Ihantola, Eeva-Mari; Hyvönen, Timo; Koivunen, Niina; Äijälä, Arttu (Association of Business Schools Finland, 2023)
Through an in-depth analysis of the benefits and challenges of full-time telecommuting experienced by accountants during the COVID-19 pandemic, we strive to enhance understanding that will help an organisation work after the pandemic. The empirical data of this qualitative case study consist of seven interviews with professional accountants (bookkeepers) in one Finnish accounting group. All of the interviewed accountants had none or litle previous experience with telecommuting. Based on the content analysis of the interviews, accountants’ experiences of telecommuting appeared to be partly equal to each other and the literature and partly different due to the perceived challenges of work and a person’s characteristics, especially the need for communication. This study deepens understanding of the importance of considering individuals’ perceptions and experiences of pandemic time telecommuting when reorganising work after the pandemic.
Keywords: telecommuting; accounting firm; accountant; bookkeeper; case study; COVID-19; fi=Henkilöstöjohtaminen|en=Human Resource Management|